Pelatihan Pemanfaatan Anorganik Menjadi Aneka Kreasi Daur Ulang di Desa Jatireja Kabupaten Bekasi: Pelatihan Pemanfaatan Anorganik Menjadi Aneka Kreasi Daur Ulang di Desa Jatireja Kabupaten Bekasi - Miftakul Huda; Nani Hartati; Nisa Nurhidayanti; Daspar Daspar (Jurnal Pengabdian Masyarakat Akademisi, 2022)
The training in this service activity aims to: (1) Knowing the role of waste recycling training services in Jatireja Village (2) Knowing the changes in society with waste recycling training in Jatireja Village and (3) Knowing the effect of waste recycling training services in Jatireja Village .The target audience for Community Service activities is the community in Jatireja Village. The method of Community Service activities is lecture as well as practice. The steps for Community Service activities are lectures to explain the study of waste, types of waste, and sources of waste, waste management and 3R (reduce, reuse, recycle), and management of inorganic waste into various recycled creations, followed by questions and answers, demonstrations of waste management. inorganic into various recycled creations, practice making various recycled creations. The supporting factors for the service activities are the support from the Village Head, the Chairperson of Family Welfare Empowerment, and the enthusiasm of the service participants, while the inhibiting factor for the activity is the limited time for the implementation of the service.Overall service activities can be said to be good and successful, seen from the success of the target number of training participants (100%), the achievement of training objectives (80%), the achievement of the planned material targets (80%), and the ability of participants in mastering the material (80%) ). Service activities can increase the knowledge of housewives and young women about the management of inorganic waste into various recycled creations and empower them in managing inorganic waste (used plastic bottles) into various recycled creations (flowers, brooches, bag decorations).